Revisión sobre los usos y variables para determinar la calidad del agua pluvial en superficies de cubierta (2015)
The article elaborates on the uses, variables and roof surfaces that guarantee the quality of rain wáter catchment systems and current technology on the subject. 50 articles related to the research are analyzed, with Asia and North America regions with the largest number of scientific publications. Most items are related to the end-use resource to rain occurs in the world, second published articles analyzing the variables rainwater for storage and potential use. And finally in lower production publications they are related to the collection surfaces in different types and cover materials.